Genome-wide association studies reveal putative QTLs for physiological traits under contrasting phosphorous conditions in wheat (Triticum aestivum L.) - Dharmateja, Palaparthi; Yadav, Rajbir; Kumar, Manjeet; Babu, Prashanth; Jain, Neelu; Mandal, Pranab Kumar; Pandey, Rakesh; Shrivastava, Manoj; Gaikwad, Kiran B.; Bainsla, Naresh Kumar; Tomar, Vipin; Sugumar, S.; et al. (Frontiers in Genetics, 2022)
A Genome-wide association (GWAS) study was conducted for phosphorous (P)-use responsive physiological traits in bread wheat at the seedling stage under contrasting P regimes. A panel of 158 diverse advanced breeding lines and released varieties, and a set of 10,800 filtered single nucleotide polymorphism (SNP) markers were used to study marker-trait associations over the eight shoot traits. Principle component analysis separated the two environments (P regimes) because of the differential response of the traits indicating the essentiality of the separate breeding programmes for each environment. Significant variations for genotypic, environmental, and genotype × environment (GEI) effects were observed for all the traits in the combined analysis of variance with moderately high broad sense heritability traits (0.50–0.73). With the different algorithms of association mapping viz., BLINK, FarmCPU, and MLM, 38 unique QTLs under non-limiting P (NLP) and 45 QTLs for limiting P (LP) conditions for various shoot traits were identified. Some of these QTLs were captured by all three algorithms. Interestingly, a Q.iari.dt.sdw.1 on chromosome 1D was found to explain the significant variations in three important physiological traits under non-limiting phosphorus (NLP) conditions. We identified the putative candidate genes for QTLs namely Q.iari.dt.chl.1, Q.iari.dt.sdw.16, Q.iari.dt.sdw.9 and Q.iari.dt.tpc.1 which are potentially involved in the mechanism regulating phosphorus use efficiency through improved P absorption due to improved root architectural traits and better mobilization such as sulfotransferase involved in postembryonic root development, WALLS ARE THIN1 (WAT1), a plant-specific protein that facilitates auxin export; lectin receptor-like kinase essentially involved in plant development, stress response during germination and lateral root development and F-box component of the SKP-Cullin-F box E3 ubiquitin ligase complex and strigolactone signal perception. Expression profiling of putative genes located in identified genomic regions against the wheat expression atlas revealed their significance based on the expression of these genes for stress response and growth development processes in wheat. Our results thus provide an important insight into understanding the genetic basis for improving PUE under phosphorus stress conditions and can shape the future breeding programme by developing and integrating molecular markers for these difficult-to-score important traits.